KAJI EKSPERIMENTAL KARAKTERISTIK ALIRAN EKSTERNAL PADA BENDA TUMPUL SEGIEMPAT DENGAN UJUNG MUKA ELLIPS - Subagyo, Rachmat (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2012)
Aerodynamic equilibrium at the vehicle can not be separated from the presence of flow separation and drag force that occurs, and is a great loss that can affect the use of waste fuels. Many ways to minimize the drag force that arises when a body drained of fluid flow, one of which is to control the boundary layer on the surface of the object or to modify the shape of the object. In this research using wind tunnel aerofoil as a tool to tes while the test object is made using teak wood in the form of ellipse as much as 5 pieces. The surface of the test object is made smooth and varnished.The results are: AlphaThe smaller the drag coefficient with the increasing Reynolds number and variety of the major axis (a) on the test object, and conversely the smaller the value of the Reynolds number and variety of the major axis is smaller drag coefficient. With different Reynolds numbers show almost the same pressure distribution of the five test specimens except the specimen 75 mm major axis variation of this happens because the influence of the capillary tube. The greater the radius of curvature or the greater variation the separasion nough major axis can be delayed can be seen in the figure based separasi point (b / a) for the fifth test object that the separation point can be delayed due to the fluid flowing in the test specimen experienced less resistance because of its shape more taper than another test.